2014
DOI: 10.1002/mrc.4101
|View full text |Cite
|
Sign up to set email alerts
|

NMR of guest‐host systems: 8CB in chiral nematic porous glasses

Abstract: Liquid crystals confined to porous materials often have different critical phenomena and ordering than in the bulk. Through the selection of pore size, structure and guest liquid crystal, these systems could enable a variety of functional materials for applications such as sensors and displays. A recent example of such a system is chiral nematic mesoporous films infiltrated with liquid crystal 4-cyano-4'-n-octylbiphenyl (8CB), which has reversible thermal switching of its optical bandgap. The optical bandgap i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…When a decrease of the index of refraction of the material occurs, the pitch of the nematic chiral phases increases due to the presence of an isotropic liquid between the layers. The effect of temperature was also observed in chiral nematic glasses impregnated with 8CB and the initial iridescence of the films was lost when the liquid crystal attains the isotropic phase. The different behavior observed for CNC/5CB composites is mainly ruled by the anchoring of the liquid‐crystal/cellulose system …”
mentioning
confidence: 84%
“…When a decrease of the index of refraction of the material occurs, the pitch of the nematic chiral phases increases due to the presence of an isotropic liquid between the layers. The effect of temperature was also observed in chiral nematic glasses impregnated with 8CB and the initial iridescence of the films was lost when the liquid crystal attains the isotropic phase. The different behavior observed for CNC/5CB composites is mainly ruled by the anchoring of the liquid‐crystal/cellulose system …”
mentioning
confidence: 84%
“…27 In another study we demonstrated reversible switching of the photonic properties of CNMO by loading its pores with a calamitic liquid crystal, 8CB (4 0 -n-octyl-4-cyano-biphenyl). 28,29 Detailed solid-state NMR spectroscopic investigations proved that the 8CB is aligned with the pores when it is in a mesophase.…”
Section: Introductionmentioning
confidence: 99%
“…They are readily modied by switching donor/acceptor motifs. Although a number of mesoporous silica composites with LCs are known, 17,29 SMLCs have not been previously investigated in mesoporous hosts. With the goal of developing temperature-sensitive photonic materials, we therefore set out to investigate SMLCs in chiral nematic mesoporous hosts.…”
Section: Introductionmentioning
confidence: 99%
“…[67][68][69] For mesoporous SBA-15 silica, the dimensionless C constant is typically between 100 and 150, indicating the high energy, polar surfaces of surface silanol groups. [70] Using pulsed-field gradient NMR diffusion measurements, the effective diffusion coefficient of absorbed water can be measured in both the longitudinal direction (D ) The films containing mixed systems of the longer alkylene-bridged and ethylenebridged precursors (Prop/Et-CNMO to the Hex/Et-CNMO) displayed lower C constants, with values ranging from ≈65 to 80.…”
Section: Surface Properties and Pore Structure Within The Organosilicmentioning
confidence: 99%